Strategic Behavior and Tourism in Fronteira da Paz: study in the lodging sector - Cassanego Junior, Paulo; Simoni, Nathalia De; Marchi, Jamur (Revista Turismo em Análise, 2013)
We tried to identify the strategic behavior of organizations in the tourism area of the conurbation Fronteira da Paz. To reach these goals, we conducted a qualitative, descriptive and exploratory research. As a method of data collection we used interviews with open questions applied to managers of organizations with constructed variables of Grangsjo (2003), Wang & Krakover (2007) and Marchi (2006) studies. From these, about the behavior of firms, we found that companies do not reach significant levels of confidence within the same sector, resulting in short and sporadic relationships, driven in part by ties of friendship, and that only occur when there is no longer possible advantage, depending on the availability of resources is limited, as occurs when there is more accommodating in its hotels.